Strengths and Weaknesses of Non‐enhanced and Contrast‐enhanced Cadaver Computed Tomography Scans in the Teaching of Gross Anatomy in an Integrated Curriculum. Issue 1 (24th February 2021) - Paech, Daniel; Klopries, Kerstin; Nawrotzki, Ralph; Schlemmer, Heinz‐Peter; Giesel, Frederik L.; Kirsch, Joachim; Schultz, Jobst‐Hendrik; Kuner, Thomas; Doll, Sara
Abstract : Cadaver‐specific postmortem computed tomography (PMCT) has become an integral part in anatomy teaching at several universities. Recently, the feasibility of contrast‐enhanced (CE)‐PMCT has been demonstrated. The purpose of this study was to identify particular strengths and weaknesses of both non‐enhanced and contrast‐enhanced PMCT compared to conventional cadaver dissection. First, the students' perception of the learning effectiveness of the three different modalities have been assessed using a 34‐item survey (five‐point Likert scale) covering all anatomy course modules. Results were compared using the nonparametric Friedman Test. Second, the most frequent artifacts in cadaver CT scans, were systematically analyzed in 122 PMCT and 31 CE‐PMCT data sets to quantify method‐related limitations and characteristics. Perfusion quality was assessed in 57 vascular segments (38 arterial and 19 venous). The survey was answered by n = 257/320 (80.3%) students. Increased learning benefits of PMCT/ CE‐PMCT compared to cadaver dissection were found in osteology (2/3 categories, P < 0.001), head and neck (2/5 categories, P < 0.01), and brain anatomy (3/3 categories, P < 0.01). Contrast‐enhanced‐PMCT was perceived particularly useful in learning vascular anatomy (10/10 categories, P < 0.01). Cadaver dissection received significantly higher scores compared to PMCT and CE‐PMCT in all categories of the abdomen and thorax (7/7 categories, P < 0.001), as well as the majority of muscular anatomy (5/6 categories, P < 0.001). Frequent postmortem artifacts (total n = 28, native‐phase n = 21, contrast injection‐related n = 7) were identified and assessed. The results of this work contribute to the understanding of the value of integrating cadaver‐specific PMCT in anatomy teaching.